Adenomatoid Odontogenic Tumor Associated with an Impacted Maxillary Lateral Incisor: A Case Report with Five-Year Follow-Up - Najwa Karam Genno; Nicole Aoun; Sami El Toum (Hindawi Limited, 2017)
Adenomatoid odontogenic tumor (AOT), a benign (hamartomatous) lesion of odontogenic origin, is an uncommon tumor which affects mainly females in the second decade. This lesion is most commonly associated with an impacted maxillary canine. This paper reported a case of AOT, in a 16-year-old female, associated with an impacted maxillary left lateral incisor. The evolution of this tumor was followed over 36 months and 24 months after excision.